HF propagation measurements during the 29 March 2006 total solar Eclipse in Turkey - Guzel, E.; Canyilmaz, M.; Ozcan, O.; Aydogdu, M. (Amer Inst Physics, 2007)
During the 29 March 2006 total solar Eclipse, the electromagnetic wave (5.47 MHz) is transmitted from Trabzon-Turkey (40,59 N; 39,43 E) and received at Antalya-Turkey (36,53 N; 30,39 E). The field strength of this wave is measured by ITU-Compliant HF Field Strength Monitoring Terminal. Observations made in the solar eclipse path. The measurements are consisted of field strength and noise at control and total solar eclipse day. It is observed that the field strength and noise are decreased during the total solar eclipse with respect to the control days.
6th International Conference of the Balkan-Physical-Union -- AUG 22-26, 2006 -- Istanbul, TURKEY
Keywords: electromagnetic wave propagation in ionosphere; solar Eclipse; field strength